Projection of Streamflow Changes Under CMIP6 Scenarios in the Urumqi River Head Watershed, Tianshan Mountain, China - Yang, Min; Li, Zhongqin; Anjum, Muhammad Naveed; Kayastha, Rakesh; Kayastha, Rijan Bhakta; Rai, Mukesh; Zhang, Xin; Xu, Chunhai (Frontiers in Earth Science, 2022)
Analyzing climate change impacts on hydrology and future water supply projections is essential for effective water resource management and planning in the large river basins of Asia. In these regions, streamflow and glacier melt are still subject to significant uncertainties due to the lack of certainty in climate change projections and modeling methods. In this study, a glacier dynamics model (the Open Global Glacier Model (OGGM)) was coupled with a glacio-hydrological model (the Glacio-hydrological Degree-day Model (GDM)) to predict possible hydrological changes in the head watershed of the Urumqi River under three Shared Socioeconomic Pathways: SSP2-4.5, SSP3-7.0 and SSP5-8.5. The GDM was calibrated and validated against in situ observed discharge data for the 2007–2011 and 2012–2018 periods; the resulting Nash-Sutcliffe efficiency (NSE) values were 0.82 and 0.81, respectively. The GDM model was driven using the ensemble of five downscaled CMIP6 data to examine the potential impacts of climate change on hydrologic processes in the basin. The GDM simulated four runoff components: the base flow, precipitation, ice melt, and snow melt. The melting of snow and ice was found to be the predominant source of runoff. During the calibration and validation periods, snow and ice melt contributed 25.64% and 30.17%, respectively, to the total runoff. Under all SSPs scenarios, the projected runoff will decrease indicate that the peak runoff time has passed. It was revealed that a 2°C increase in the monthly average temperature would result in a 37.7% increase in the total discharge of the basin. Moreover, the GDM was revealed to be more responsive to changes in air temperature than to changes in glacier extent.